Performance characterization of dual-task in community dwelling elderly people and mild vascular cognitive impairment - Mateus, Mariana Isabel Abreu da Silva, 1991- (2019)
Tese de mestrado, Neurociências, Universidade de Lisboa, Faculdade de Medicina, 2019